The Indigenous languages of South America : a comprehensive guide - Campbell, Lyle; Grondona, Verónica María (World of linguistics, 2012)
"The Indigenous Languages of South America: A Comprehensive Guide is a thorough guide to the Indigenous languages of this part of the world. With more than a third of the linguistic diversity of the world (in terms of language families and isolates), South American languages contribute new findings in most areas of linguistics. Though formerly one of the linguistically least known areas of the world, extensive descriptive and historical linguistic research in recent years has expanded knowledge greatly. These advances are represented in this volume in indepth treatments by the foremost scholars in the field, with chapters on the history of investigation, language classification, language endangerment, language contact, typology, phonology and phonetics, and on major language families and regions of South America"--Provided by publisher.